ESG analysis: case study in a tourism company - Silva, Keren Karolyne Nóbrega (Brazilian Journal of Production Engineering, 2023)
The tourism sector is one of the main responsible for socioeconomic growth, however, this sector still has a gap in environmental bias, for this reason, the concept of sustainable tourism has been stimulated, through the adoption of circular principles or the implementation of tools that help this transition, such as the TBL and ESG philosophy. In this sense, the present research aims to identify sustainable practices in a tourism company, in order to enhance sustainable development. To achieve this, the case study was conducted to contribute to the environmental scenario, without forgetting the influence of the socioeconomic environment, ensuring that the sector continues to grow despite the adaptation measures. Therefore, the results showed that the object of study has gaps that can be resolved with the principles of circularity, so that improvement actions are presented for the organization under study.
Keywords: sustainable tourism; ESG; TBL